A magyarországi légiháború és a magyar zsidók deportálásának kapcsolatai a II. világháború idején = The connection between the deportation of Hungarian Jews and the air war over Hungary during World War 2 - Oláh András Pál (Belvedere Meridionale, 2018)
In my study I examined the connection between the deportation of Hungarian Jews and the air war over Hungary (including the Allied Psywar) during World War 2. My conclusion is that although the mass deportation of Hungarian Jews was stopped by the intervening of Regent Miklós Horthy, he did not do so due to the Allied propaganda leaflets or the destruction caused by Allied bombs. He was forced to act by the worrying foreign and home news condemning the Hungarian government.